Cosmological, Astronomical and Astrological Elements in Sermons of Seventeenth-Century Ruthenian Authors - Olga Čadajeva (Teorie vědy, 2020)
The development of oral preaching and the genre of sermon in seventeenth-century Russia was primarily brought about by Ruthenian authors influenced by the Latin tradition, e.g., Ioannikiy Galyatovsky, Lazar Baranovych and Simeon Polotsky. These authors incorporated their general knowledge of cosmology, astronomy and astrology into their homilies, which present a valuable insight into the intellectual background of the period through the prism of cosmological elements used mostly as parts of rhetoric constructions. While the functions of the particular elements of natural philosophy varied in different authors, they shared certain concepts common to both scholastic thought and Baroque aesthetics. Despite being considerably distant from seventeenth-century science, the homilies also served educational purposes and may be perceived as a step towards the Westernisation and secularisation of Russian culture.